2017
DOI: 10.1371/journal.ppat.1006464
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori gene silencing in vivo demonstrates urease is essential for chronic infection

Abstract: Helicobacter pylori infection causes chronic active gastritis that after many years of infection can develop into peptic ulceration or gastric adenocarcinoma. The bacterium is highly adapted to surviving in the gastric environment and a key adaptation is the virulence factor urease. Although widely postulated, the requirement of urease expression for persistent infection has not been elucidated experimentally as conventional urease knockout mutants are incapable of colonization. To overcome this constraint, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 73 publications
1
56
0
Order By: Relevance
“…H. pylori infection is a threat to human health, for example, the long-term colonization of H. pylori in the stomach can change PH of the stomach, promote chronic gastritis, gastric ulcers, even gastric cancer [2]. However, until now, the mechanism of H. pylori -associated chronic gastritis remains unclear, and it is believed that the interplays between host and bacterial virulence factors [14,20], such as VacA [21], urease [22], especially a major virulence factor cagA that can be injected into host cell by Type IV Secretion System (T4SS) [23], and the following persistent inflammation are likely the underlying causes.…”
Section: Discussionmentioning
confidence: 99%
“…H. pylori infection is a threat to human health, for example, the long-term colonization of H. pylori in the stomach can change PH of the stomach, promote chronic gastritis, gastric ulcers, even gastric cancer [2]. However, until now, the mechanism of H. pylori -associated chronic gastritis remains unclear, and it is believed that the interplays between host and bacterial virulence factors [14,20], such as VacA [21], urease [22], especially a major virulence factor cagA that can be injected into host cell by Type IV Secretion System (T4SS) [23], and the following persistent inflammation are likely the underlying causes.…”
Section: Discussionmentioning
confidence: 99%
“…26 27 While urease appeared to be less essential after established colonization, chronic infection was restored by a positive selection process that altered the repressor protein, supporting a continual requirement for urease. 27 This approach may be applied to other virulence factors for understanding their roles under certain conditions, in either in vitro or in vivo studies. Additional initial colonization factors studied included GGT and RhpA, an RNA helicase protein, mutants of which showed colonization attenuation in the animal model.…”
Section: Non-cag Virulence Factorsmentioning
confidence: 99%
“…A new gene‐silencing technique using the modification of the ure A promoter with a tet ‐system developed by Debowski et al. shed new insight on the role of urease during chronic infection . While urease appeared to be less essential after established colonization, chronic infection was restored by a positive selection process that altered the repressor protein, supporting a continual requirement for urease .…”
Section: Virulence Factorsmentioning
confidence: 99%
“…This recombinant experiment was fashioned in H. pylori and the gene expression was regulated . This gene silencing experiment concluded that the loss of urease activity could prove to be pernicious for H. pylori …”
Section: Ureasementioning
confidence: 99%